2023
DOI: 10.1007/s11123-023-00663-6
|View full text |Cite
|
Sign up to set email alerts
|

Trade for catch-up: examining how global value chains participation affects productive efficiency

Abstract: A substantial part of production and trade now takes place through global value chains (GVC), making it an essential conduit of knowledge spillover and technology transfer. Yet, extant studies examining how countries become productively efficient and catch-up to the global efficiency frontier through international trade have ignored the possible role of GVC in fast-tracking this process. This paper provides the first empirical evidence that fills this knowledge gap. We propose a two-stage empirical strategy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…In this study, the “ production approach ” in financial institutions (Phan et al , 2018; Degl’Innocenti et al , 2017; Shawtari et al , 2015) was considered to select the most adequate set of inputs and outputs for the telecommunications companies (Wanke and Barros, 2016). As suggested in previous studies (Ndubuisi and Owusu, 2023; Ndubuisi et al , 2022), the DEA model we deployed assumed that two outputs were produced by three inputs. Broadly, from a production perspective, telecommunications companies are viewed as firms that generate sales revenues using their assets.…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the “ production approach ” in financial institutions (Phan et al , 2018; Degl’Innocenti et al , 2017; Shawtari et al , 2015) was considered to select the most adequate set of inputs and outputs for the telecommunications companies (Wanke and Barros, 2016). As suggested in previous studies (Ndubuisi and Owusu, 2023; Ndubuisi et al , 2022), the DEA model we deployed assumed that two outputs were produced by three inputs. Broadly, from a production perspective, telecommunications companies are viewed as firms that generate sales revenues using their assets.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Similar to Oredegbe and Zhang (2020), Giokas and Pentzaropoulos (2008) conducted a study on 30 countries. Recent studies (Ndubuisi et al, 2022;Ndubuisi and Owusu, 2023;Ndubuisi et al, 2021) in the telecommunications industry have confirmed that the envisaged relationship between ICTs capabilities and technical efficiency is conditioned by a country's characteristics, such as levels of education, institutional quality and macroeconomic conditions, as captured by the inflation rate.…”
Section: Analytical Hierarchy Process Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Countries in the early stages of development are located far from the technological frontier, and they have more room to benefit from knowledge transfers or spillover effects via GVC participation. Thus, they are able to 'catch up' with the global efficiency frontier [42]. Using a panel estimation covering 47 countries and 13 manufacturing sectors from 1995 to 2011, Urata (2020) notes that developing countries benefit more from improved productivity when they source intermediate goods from advanced countries and engage in backward GVC participation [43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the first phase of GVCs emergence, dating approximately until the 2008 economic crisis, the literature mostly pointed to the apparently globally widespread benefits of GVCs involvement. In developing countries, the involvement in GVCs gave access to new productive and technological capabilities, raising productivity and leading to economic and social upgrading (Ndubuisi and Owusu, 2023; Pahl and Timmer, 2020). In developed countries, the involvement in GVCs was expected to open paths for upgrading domestic technological capabilities (Verspagen, 2010) and for shifting towards more complex patterns of innovation (Capello and Lenzi, 2013).…”
Section: Introductionmentioning
confidence: 99%